Health risk effect of indoor air quality index at adaptive reused museum in Malaysia - Mohd Dzulkifli, Syahrun Niezam (2019)
To this date, there are still limited studies conducted on the risk assessment of the indoor air quality (IAQ) which affect towards the people in the public building, especially in the museum. As one of the environmental risk assessment tool, the environmental quality index was utilised to determine whether the current location provides a healthy environment or not. Therefore the purpose of this study is to develop an index, called IAQ Index (InAQI), as a health risk assessment tool for the people, especially for visitors, for a short term period at the adaptive reused museum in Malaysia. In this study, the mixed-mode method was used to fulfil the objectives of the study by using a qualitative method and quantitative method. For qualitative method, there is only one data collection technique involve in this study which is a walkthrough inspection (observation method), while for quantitative method, there are two types of data collection techniques which are subjective measurement (questionnaire survey) and physical measurement (indoor environment variables measurements). The physical measurement was conducted on the adaptive reused museum and at the same time the subjective measurement were distributed to the visitors. The results of the study indicated that the IAQ condition for gaseous pollutant of NO2, SO2 and CO2 and particulate matter of PM2.5, exceeded the acceptable Threshold Limit Value. Subsequently, to develop a representative human health index based on the indoor environment, the InAQI regression equation was established, using statistical approach, by integrating the factor of IAQ variables and Sick Building Syndrome (SBS) perception. Apart from that, the InAQI regression equation was verified through the execution of the actual case study by comparing the observed and predicted outputs. These verifications have shown that the InAQI may be suitably applied at all adaptive reused museums, especially in Malaysia, to rank the health risk effect towards visitors that associates well with the IAQ and SBS symptom.